A Comparative Analysis of the Degree of Fiscal Decentralisation Between the City of Jambi and Batanghari Regency - Dewi Purnama Sari; Nurhayani; Parmadi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Fiscal decentralisation is a key instrument in the implementation of regional autonomy, aimed at enhancing the financial independence of local governments. The success of fiscal decentralisation can be measured by a region’s ability to optimise its own-source revenue (PAD) and reduce its dependence on central government transfers. This study aims to analyse the degree of fiscal decentralisation and identify differences in fiscal capacity between the City of Jambi and Batang Hari Regency during the period 2020–2024. The study employs a quantitative approach using a descriptive comparative method. The data used consists of secondary data obtained from the Budget Implementation Reports (LRA) of the City of Jambi and Batang Hari Regency. The analysis was conducted using ratios of the degree of fiscal decentralisation based on Local Own-Source Revenue (PAD), Tax and Non-Tax Revenue Sharing (BHPBP), and central government transfers. Furthermore, differences in the fiscal capacity of the two regions were analysed using an independent samples t-test. The results indicate that Jambi City possesses a higher level of fiscal autonomy compared to Batang Hari Regency, as evidenced by a relatively higher contribution of PAD to total regional revenue. Conversely, Batang Hari Regency exhibits a greater degree of dependence on revenue-sharing funds and central government transfers. The results of the t-test also indicate a significant difference in the degree of fiscal decentralisation between the two regions. These findings suggest that regional economic characteristics and the capacity to manage local revenue sources play a significant role in determining the level of fiscal autonomy of local governments.